Occurrence of gastrointestinal parasites in cattle in Indonesia. Issue 1 (March 2021) - Nurcahyo, R W; Ekawasti, F; Haryuningtyas, D; Wardhana, A H; Firdausy, L W; Priyowidodo, D; Prastowo, J
Abstract: Gastrointestinal nematode parasites play an important role in cattle farming in Indonesia. The majority of parasite infection cases cause weight loss and decreases in appetite, productivity, milk production and farmers' economic income. This study aimed at finding out the incidence of gastrointestinal nematode parasite disease in cattle at several regions in Indonesia. It was conducted in the period of March 6 th to October 2020. There were totally 335 samples randomly drawn from various regions in 15 provinces of 34 provinces in Indonesia. Stool was examined using Whitlock and flotation methods. The results showed that the prevalence of gastrointestinal nematodes Strongyle, Trichuris sp., Capillaria sp., and Ascaris sp. amounted to 24.2%. The highest prevalence of the Strongyle nematodes was found in West Nusa Tenggara (52%), Central Kalimantan (50.8%) and Southeast Sulawesi (40%). The prevalence of the Trichuris sp. in East Java was 15%, while it was 10% in Central Kalimantan. The prevalence of the Capillaria sp. in North Kalimantan was 21.1%, in West Sumatra 18.8% and in East Java 6.7%. The prevalence of the Ascaris sp. worms in East Java was 16.7%. The results of the characterization based on age, sex and cattle management showed that 4.6% of the Strongyle worms were found in bulls, 2.74% in females, 4.38% in intensive maintenance and 2.47% in semi-intensive maintenance, while 5.48% of the worms were found in adult cattle and 1.37% in young cattle. The same pattern was observed in Trichuris sp., Capillaria sp. and Ascarids sp. infections. The results indicated the need for the eradication of the gastrointestinal nematodes through deworming and good management system.